AWARENESS OF MALARIAL TRANSMISSION BASED ON A SURVEY IN KOLKATA (International Journal of Food and Nutritional Sciences, 2023)
Introduction: A female Anopheles mosquito carrying the malaria parasite bites a human as the bug gathers her blood meal to start the Plasmodium species infection process. Despite notable gains and advancements in human health and the reduction of the disease's burden, malaria continues to be a serious public health issue. It is among the top ten leading causes of illness and death in a variety of age groups, including adults and children below the age of five. In South-East Asia, particularly India, malaria is still a significant public health issue. Malaria affects about 36.3% of the world's population in 91 nations. India accounts for 76.5% of the 2.5 million cases of malaria in the South-East Asian region, which contributes to the overall malaria burden.Aims and Objectives: To evaluate and analyze the awareness of malaria through surveying and to determine the hemoglobin level among the population of Kolkata.Methods: This survey was concluded in Kolkata city in India from December, 2021 to December, 2022. The researcher surveyed 2300 participants from communities in Kolkata and had classified two categories to the participants who had past history of malaria they determined positive Microscopic demonstration and who had no past history they identified negative Microscopic demonstration. Moreover, the researcher had collected 1125 participants of positive Microscopic demonstration and 1175 participants of negative Microscopic demonstration .Results: Throughout the in-depth analysis, the researcher had presented a few survey questions such as sources of drinking water, sources of water, purpose of other activities , use of mosquito net among the positive and negative Microscopic demonstration.The researcher had recognised the hemoglobin level of positive Microscopic demonstration and negative Microscopic demonstration. Conclusion: Moreover, this survey had concluded that through this in-depth analysis, it had demonstrated several methods of preventing malaria. It used 1125 participants for positive Microscopic demonstration and 1175 of participants of negative Microscopic demonstration to conclude this argument. Moreover, this survey was effective for researchers to increase the awareness of malaria prevention.